Developing Autonomous Observing Systems for Micronutrient Trace Metals - Grand, Maxime M.; Laes-Huon, Agathe; Fietz, Susanne; Resing, Joseph A.; Obata, Hajime; Luther, George W.; Tagliabue, Alessandro; Achterberg, Eric P.; Middag, Rob; Tovar-Sánchez, Antonio; Bowie, Andrew R. (Frontiers in Marine Science, 2019)
Trace metal micronutrients are integral to the functioning of marine ecosystems and the export of particulate carbon to the deep ocean. Although much progress has been made in mapping the distributions of metal micronutrients throughout the ocean over the last 30 years, there remain information gaps, most notable during seasonal transitions and in remote regions. The next challenge is to develop in situ sensing technologies necessary to capture the spatial and temporal variabilities of micronutrients characterized with short residence times, highly variable source terms and sub-nanomolar concentrations in open ocean settings. Such an effort will allow investigation of the biogeochemical processes at the necessary resolution to constrain fluxes, residence times and the biological and chemical responses to varying metal inputs in a changing ocean. Here, we discuss the current state of the art and analytical challenges associated with metal micronutrient determinations and highlight existing and emerging technologies, namely in situ chemical analyzers, electrochemical sensors, passive preconcentration samplers and autonomous trace metal clean samplers, which could form the basis of autonomous observing systems for trace metals within the next decade. We suggest that several existing assets can already be deployed in regions of enhanced metal concentrations and argue that, upon further development, a combination of wet chemical analyzers with electrochemical sensors may provide the best compromise between analytical precision, detection limits, metal speciation and longevity for autonomous open ocean determinations. To meet this goal, resources must be invested to: (1) improve the sensitivity of existing sensors including the development of novel chemical assays; (2) reduce sensor size and power requirements; (3) develop an open-source “Do-It-Yourself” infrastructure to facilitate sensor development, uptake by end-users and foster a mechanism by which scientists can rapidly adapt commercially available technologies to in situ applications; and (4) develop a community-led standardized protocol to demonstrate the endurance and comparability of in situ sensor data with established techniques. Such a vision will be best served through ongoing collaborations between trace metal geochemists, analytical chemists, the engineering community and commercial partners, which will accelerate the delivery of new technologies for in situ metal sensing in the decade following OceanObs’19.